Strategi Pemerintah Daerah dalam Meningkatkan Pelayanan pada Masyarakat Melalui Sistem Pemerintahan Berbasis Elektronik - Widya Kurniati Mohi; Nuzlan Botutihe (Universitas Muhammadiyah Gorontalo, 2020)
This article aims to analyze and find out the strategies implemented by the Regional Government, especially the Kelurahan Governments in Gorontalo District in providing maximum service to the community. This study uses qualitative research methods with the intention of comprehensively knowing several things related to the implementation of E-Gov and to reveal the phenomena that occur in the application of E-Gov. The results showed that the capacity or ability of the Gorontalo District government in implementing the ¬E-Gov concept needs to be evaluated and continuously improved, especially in relation to the budget. This can be seen from the limited funds that are not allocated specifically for the Electronic Government, the limited allocation of funds that have been budgeted by the Government in Gorontalo District is still insufficient for E-Government development, so that activities carried out follow the amount of the budget given, in other words the budget can affect effectiveness of the implementation of activities carried out in the application of E-Government, so that the use and utilization of the budget must be effective and efficient. the implementation of E-Gov in Gorontalo District has been going well. However, there are still some obstacles that are faced, this can be seen from the human resources recruited to manage the Electronic Government who do not have the competence and expertise in this field and some do not even have expertise in the technology field. This is a big challenge for the Gorontalo District governmentArtikel ini bertujuan menganalisis dan mengetahui strategi yang dilakukan Pemerintah Daerah khususnya Pemerintah Kelurahan yang ada di Kabupaten Gorontalo dalam memberikan pelayanan yang maksimal kepada masyarakat. Penelitian ini menggunakan metode penelitian kualitatif dengan maksud untuk mengetahui secara komprehensif beberapa hal terkait dengan pelaksanaan E-Gov dan mengungkap fenomena yang terjadi dalam penerapan E-Gov. Hasil penelitian menunjukkan kapasitas atau kemampuan pemerintah Kabupaten Gorontalo dalam menerapkan konsep E-Gov perlu dilakukan evaluasi dan terus ditingkatkan terutama terkait dengan anggaran. Hal ini terlihat dari keterbatasan dana yang tidak dialokasikan khusus untuk Electronic Government,terbatasnya alokasi dana yang telah dianggarkan oleh Pemerintah di Kabupaten Gorontalo masih belum mencukupi untuk pengembangan E-Government, sehingga kegiatan yang dilakukan mengikuti jumlah anggaran yang diberikan, dengan kata lain anggaran dapat mempengaruhi efektivitas pelaksanaan kegiatan yang dilakukan di dalam penerapan E-Government, sehingga penggunaan dan pemanfaatan anggaran harus efektif dan efisien.penerapan E-Gov di Kabupaten Gorontalo sudah berjalan dengan baik. Namun, masih ada beberapa kendala yang dihadapi, hal ini dapat dilihat dari sumber daya manusia yang direkrut dalam mengelola Electronic Government belum memiliki kompetensi dan keahlian di bidang tersebut bahkan ada yang tidak memiliki keahlian di bidang teknologi